PARTISIPASI MASYARAKAT DALAM KEGIATAN PEMBANGUNAN JALAN PERTANIAN DI AERTRANG KELURAHAN MALALAYANG I TIMUR MANADO - Isaura Gabriela Engka; Charles R. Ngangi; Caroline B. D. Pakasi (Sam Ratulangi University, 2015)
The purpose of this research is to know the forms of community participation of farmers and non-farmers in the Agricultural Road construction Aertrang Malalayang 1 East Village in the Manado City. The benefits of this research are: research is expected to provide information for the public and education about the forms of participation of farmers and non-farmers in agriculture road construction in the Village of Aertrang Malalayang 1, Manado City. This research collect primary dan secondarydata. Primary data collection through direct face to face interviews and field observations (observation) to 20 respondents using questionnaires. The analytical method used in this research is qualitative descriptive analysis method. The results of the study are presented in tabular form. The findings in this study are: (1) The forms of community participation in development activities of agricultural roads in the village Malalayang I Aertrang East, namely: labor, money, materials such as cement, stone and sand. And also, provision of consumption / food to the community members who do the work of farm road construction, (2) community members actively involved in agricultural road construction activities in the Village Malalayang I Aertrang East.